2015
DOI: 10.1039/c5ra23483b
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of dialkylphosphinic acids and a structure–reactivity study in rare earth metal extraction

Abstract: Dialkylphosphinic acids were synthesized efficiently under microwave irradiation. The extractants with ethyl or propyl substituents at the β-position showed higher separation efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…49 Namely, the ΔG EX and K EX are difficult to calculate. Consequently, in previous reports, 47,48 a simplified chemical reaction…”
Section: Experiments and Computation Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…49 Namely, the ΔG EX and K EX are difficult to calculate. Consequently, in previous reports, 47,48 a simplified chemical reaction…”
Section: Experiments and Computation Sectionmentioning
confidence: 99%
“…As indicated in our previous reports, ΔG EX,1 and K EX,1 calculated from density functional theory (DFT) share the same trend with ΔG EX and K EX tested from the experimental approach. 47,48 Therefore, ΔG EX,1 is also applied to estimate ΔG EX in the trend in this work, as shown as Figure 1. The distorted conformation was adopted for the ligand in [Co(H 2 O) 5 A] (o) + to reflect the steric effect of alkyl group in extractants, especially the αor β-substituted alkyl group.…”
Section: Experiments and Computation Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The class of dialkylphosphinic acid extractants is considered to be one of the most important research aspects to develop new extractants. Recent research showed that the extraction ability of dialkylphosphinic acids depends largely on the structure of the alkyl substituent 10,11 . It can be a wide range from significantly higher than that of P507 to lower than that of Cyanex 272 12 .…”
Section: Introductionmentioning
confidence: 99%
“…It can be a wide range from significantly higher than that of P507 to lower than that of Cyanex 272 12 . However, the exploration of novel dialkylphosphinic acid extractants is restricted to the commercial olefin structure 10,12,13,14,15,16 . Though dialkylphosphinic acid extractants can also be synthesized by the Grignard-reaction method, the reaction conditions are rigorous 12,17 .…”
Section: Introductionmentioning
confidence: 99%